Prevalence of mandibular third molar impaction pattern in a private dental clinic of Sultanpur Lodhi - Kaur, Pushappreet (International Journal of Health, 2015)
Background: Mandibular third molar is the most commonly impacted tooth, and its removal is a frequently performed dentoalveolar procedure. It is important to know the prevalence rate in a particular community.Objective: This article aims at evaluation of angulation, ramus relationship and depth of impacted mandibular third molars among patients visiting a private dental clinic in Sultanpur Lodhi.Methodology: 150 patients presenting with 228 cases of lower third molar impaction were included within this study. IOPAR and where necessary, OPG was used for radiographic assessment. Age, sex and tooth number were recorded in each patient on a specially designed performa. Angulation was determined using winter’s method whereas assessment of ramus relationship and depth was done using Pell and Gregory's method.Results and Conclusion: The age of patients ranged from 21-43 years with mean age of 26.6 years. Males showed preponderance to mandibular M3 impaction (54%) in our study, and right side was found more frequently involved (53%). Radiographic assessment revealed that mesioangular impaction (45.2%) was the most prevalent angular pattern followed by vertical, distoangular and horizontal types, and Class 2 Position A (29.4%) most common and Class 1 Position C the least common type of impaction depth and ramus relationship.